The Movement of Fusarium oxysporum f.sp. cubense (Sub-Tropical Race 4) in Susceptible Cultivars of Banana - Warman, Noeleen M.; Aitken, Elizabeth A. B. (Frontiers in Plant Science, 2018)
Fusarium wilt, caused by the fungus Fusarium oxysporum f.sp. cubense (Foc), is one of the most important and destructive diseases in banana crops worldwide. There have been numerous studies into the infection process of this soil-borne pathogen; however, the extent of research into the movement of the pathogen through the rhizome and into the rest of the plant is limited. Furthermore, little is known about the movement of the pathogen once it reaches the aerial components of the plant. A strain of Foc sub-tropical race 4, genetically transformed with green fluorescent protein (GFP) gene, was used to monitor the movement of the pathogen through two susceptible cultivars, Cavendish ‘Williams’ (Musa AAA) and Lady Finger (Musa AAB). Visualisation of the pathogen in planta demonstrated its presence in the roots, the rhizome and in the outer leaf sheaths of the pseudostem prior to the appearance of external symptoms. Within the non-senescing leaf sheaths, the migration of Foc was confined to the xylem vessels; this included those where the vascular tissue was visibly discoloured, as well as those, which were apparently healthy. As senescence of leaf sheaths occurred, chlamydospores developed within the gas spaces, while formation of sporodochia and hyphal growth were apparent on the outer surface of senescing leaf sheaths. These results generate a greater understanding of the epidemiology of Foc, providing much needed knowledge to assist in the future management of Fusarium wilt incursions, as well as enhancing protocols for ongoing on-farm hygiene and biosecurity.